2013
DOI: 10.1007/s00134-013-2997-6
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive broad-spectrum treatment for ventilator-associated pneumonia in high-risk patients

Abstract: A pre-emptive approach with broad-spectrum antibiotics may be effective in reducing the incidence and delaying the onset of VAP + VAT after MHS. The ecological consequences have to be carefully evaluated in future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0
2

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…Getting back to the current study by Bouza et al [2], their findings add information that 3 days of therapy is associated with increased resistance to linezolid. We know that more than 2 days of antimicrobial agents can be associated with increased resistance [14], modifying gut flora.…”
Section: Editorialsupporting
confidence: 63%
See 1 more Smart Citation
“…Getting back to the current study by Bouza et al [2], their findings add information that 3 days of therapy is associated with increased resistance to linezolid. We know that more than 2 days of antimicrobial agents can be associated with increased resistance [14], modifying gut flora.…”
Section: Editorialsupporting
confidence: 63%
“…We commend Bouza et al [2] for addressing a perplexing intensive care problem, that of ventilatorassociated pneumonia (VAP). They randomised postoperative cardiac surgical patients to either 3 days of prophylactic antibiotics (meropenem and linezolid) or ''standard of care''.…”
mentioning
confidence: 99%
“…These principles lead to the observation that combination antimicrobial therapy may be the preferred option for empirical therapy [2]. A recent Spanish study demonstrated that a pre-emptive approach with meropenem and linezolid for 3 days was effective in reducing the incidence and delaying the onset of ventilator-associated pneumonia (VAP) in very high risk patients admitted to ICU [13]. However, in the same study, the authors reported the selection of linezolid-resistant staphylococci after the study period.…”
mentioning
confidence: 99%
“…However, in the same study, the authors reported the selection of linezolid-resistant staphylococci after the study period. The ecological consequences have to be carefully evaluated when this strategy is used [13].…”
mentioning
confidence: 99%
“…Bronchial bacterial colonization has been widely investigated in patients with chronic lung disease and, following this hypothesis, Ioanas et al [6] performed bilateral protected specimen brush and lung tissue biopsy during surgical procedures on patients with resectable lung cancer and found that almost half of them presented with bronchial colonization with at least one potential pathogenic micro-organism. Based on this strategy, Bouza et al [7] performed a prospective randomized open-label study of major heart surgery (MHS) patients requiring MV for [48 h with the use of preemptive broad-spectrum treatment, and this strategy did not reduce the incidence of VAP but increased the rate of resistant pathogens.…”
mentioning
confidence: 99%